Age and gender differences and construct of the children's emotional intelligence - Mirza, Mojgan; Redzuan, Ma'rof (Marsland Press, 2010)
With respect to the age and gender the children’s emotional intelligence construct is still being developed with little empirical support. Hence, this research follows a specific objective for determination of the differences between construct of the children’s’ emotional intelligence (EI) and their personal characteristics such as age and gender. The present study was carried out among 107 Iranian students in the Iranian primary schools in Kuala Lumpur, Malaysia. The students (girls and boys) were clustered in three different age groups, 8, 9, and 10 years old. Data were collected using the Emotional Quotient Inventory Youth Version (Bar- on EQ-i; YV, 2000) and demographic questionnaire. The statistical findings, with respect to gender and ages, indicated that there was a noticeable difference between emotional intelligence of girls and boys in groups of ages.